Blood microcirculation under conditions of a translational model of alcohol cardiomyopathy in rats - S. A. Kryzhanovskii; I. B. Tsorin; E. O. Ionova; S. A. Simonenko; M. B. Vititnova (LLC "Publisher OKI", 2024)
Purpose of the study. Studying the blood microcirculation characteristics in the brain and heart of rats with ACM.Materials and methods. The study was carried out on white outbred male rats. The animals were randomized into 2 groups: 1st (n = 7) - control (intact) rats that received a normal diet and free access to water; 2nd (n = 6) - animals that received a normal diet and a 10 % ethanol solution as the only source of liquid. After 24 weeks of alcoholization in animals, the size and inotropic function of the heart were assessed using echocardiography. The next day, in anesthetized rats (urethane 1300 mg/kg i.p.), blood microcirculation in the heart and brain was recorded using a computerized laser analyzer "LAZMA-D" (manufactured by NPP "Lazma", Russia) using the LDF 3.0.2.396 program. Using spectral wavelet analysis, the amplitudes of endothelial, neurogenic, myogenic, pulse and respiratory oscillations of microblood flow and the shunting index were determined.Results. According to echocardiography data, in rats that consumed a 10 % ethanol solution for 24 weeks, ACM is formed, which is accompanied by a decrease in blood microcirculation in the brain and myocardium. Thus, if in control animals the indicator of blood microcirculation in the myocardium was 36.60±2.19 perf. u., then in rats with ACM it was equal to 26.88±1.50 perf. u. units (p = 0.004). In the myocardium of rats with ACM, compared with control animals, the amplitude of both active and passive oscillations of microblood flow was significantly greater.Conclusion. In rats with ACM, the level of blood microcirculation in the heart muscle is significantly reduced, which, according to the results of spectral wavelet analysis, is prognostically unfavorable.